Tinjauan atas Fungsi Pengaruh Customer Service Terhadap Kepuasan Nasabah Pada PT. Bank Central Asia, Tbk. KCP Pasar Tanah Abang, Jakarta. - Siti Balqis; Imhar (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Abstract. The purpose of this study is to obtain a clear picture of the Influence of Customer Service Quality on Customer Satisfaction at PT. Bank Central Asia, Tbk, KCP Pasar Tanah Abang, Jakarta. The research was conducted starting in July 2022 by working directly at Bank BCA Pasar Tanah Abang, Jakarta. The method used to analyze data from research results is to use qualitative and quantitative methods. Providing services is a good step in increasing customer satisfaction, in line with Bank Central Asia's objectives. To analyze the relationship between the variable service stages (X) and customer satisfaction (Y), namely knowing the strength or weakness of the relationship between factor X (Service Stages) and factor Y (Customer Satisfaction), then multiple regression efficient analysis, multiple correlation coefficients, coefficients are used. multiple correlation, determinant coefficient and hypothesis testing. From the results of the regression calculation Y = 7.9 – 0.63 X1 + 1.2 X2 means that if X1 and X2 = 0, then customer satisfaction is 7.9. From the results of the correlation analysis, the value of r = 0.69 shows that there is a strong and positive relationship between ATM services and customer satisfaction by 48% while other factors are 52%. From the analysis of the t test, between stage services and ATM services obtained + count 4.91 <t table 2.05 means that Ha is accepted Ho is rejected, meaning that stage services and ATM services have a relationship with customer satisfaction.